2005
DOI: 10.1002/dvdy.20445
|View full text |Cite
|
Sign up to set email alerts
|

GCN5 and p300 share essential functions during early embryogenesis

Abstract: Previous studies revealed that deletion of genes encoding the histone acetyltransferases GCN5, p300, or CBP results in embryonic lethality in mice. PCAF and GCN5 physically interact with p300 and CBP in vitro. To determine whether these two groups of histone acetyltransferases interact functionally in vivo, we created mice lacking one or more alleles of p300, GCN5, or PCAF. As expected, we found that mice heterozygous for any single null allele are viable. The majority of GCN5 ϩ/Ϫ p300 ϩ/Ϫ mice also survive to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 73 publications
(112 reference statements)
0
24
0
Order By: Relevance
“…Together, the data support the view that there are intrinsic differences in the tumor suppressor functions of CBP and p300, even though the contributing environmental and genetic factors required for T-cell lymphomagenesis in the absence of CBP are unclear and somewhat variable. In this regard, it has recently been shown that p300 levels can vary in different mouse strains, suggesting that the combined dosage of CBP and p300 protein may also fluctuate and lead to variable phenotypic penetrance (158).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, the data support the view that there are intrinsic differences in the tumor suppressor functions of CBP and p300, even though the contributing environmental and genetic factors required for T-cell lymphomagenesis in the absence of CBP are unclear and somewhat variable. In this regard, it has recently been shown that p300 levels can vary in different mouse strains, suggesting that the combined dosage of CBP and p300 protein may also fluctuate and lead to variable phenotypic penetrance (158).…”
Section: Resultsmentioning
confidence: 99%
“…So other cofactors may only be able to compensate under a limited number of situations. The identities of such factors are unknown, although recent genetic studies demonstrate that the combined dosage of various histone acetyltransferase proteins harboring bromodomains (p300 and Gcn5, and p300 and P/CAF) are not generally limiting for mouse development (158).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Gcn5 and PCAF proteins each interact physically with p300 and CBP (Xu et al, 1998). Although mice heterozygous for either a Gcn5 or a p300 null allele are viable, Gcn5 p300 double heterozygotes exhibit reduced viability, confirming these HATs share some essential functions (Phan et al, 2005).…”
Section: Introductionmentioning
confidence: 93%
“…Our previous work indicated that Gcn5 is required for early embryogenesis and that it shares functions with p300 during development (Xu et al, 2000;Phan et al, 2005). We have also shown that mouse embryos homozygous for point mutations in Gcn5 that eliminate its acetyltransferase activity exhibit defects in cranial neural tube closure and die by E16.0 (Bu et al, 2007).…”
Section: Introductionmentioning
confidence: 94%
“…Mice heterozygous for the Gcn5 null allele are viable, as are most mice heterozygous for a p300 deletion. However, a substantial portion of mice heterozygous both Gcn5 and p300 null alleles die in utero, indicating that a critical dosage of these two HATs must be maintained during development (Phan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%